A Physicist Description of Indigenous Telecobalt Machine Bhahbhatron-II Taw (Global Journal of Science Frontier Research, 2015)
The newly designed indigenous Bhabhatron-II is installed in our institution. The Telecobalt machines were put into use for Radiotherapy after the possibility of producing High activity sources with smaller dimension which satisfies the ideal requirement of Teletherapy source. The Bhabhatron II head can accommodate nearly 250RMM source strength. Being a computer controlled machine the Bhabhatron machine differs from other conventional Telecobalt machines. This machine has advanced features such as asymmetric collimators, motorized wedge etc. This unit has keypad attached at both sides of the couch that also has digital display. The patient treatment is computer controlled. The plan parameters can be entered in the console computer and the exposure time can be programmed. This unit suits well for developing countries provided the cost of the source shall be maintained cheaper.
Keywords: bhabhatron ii; asymmetric collimators; indigenous